Pusat Rehabilitasi Pasca Stroke di Semarang dengan Pendekatan Healing Environment - Wijanarko, Agung, Ronim Azizah, ST. MT (2016)
Post-Stroke Rehabilitation Center is a rehabilitation center that handles patients with post- stroke as well an educational tool for visitors to be able to know how to prevent stroke appear. In addition, there are the facilities to support all the activities in it. Patients and visitors can also feel the comfort of a healing garden is there to support rehabilitation activity in it. Semarang is a metropolitan city with a fairly high level of activity that sometimes makes inhabitants become negligent in maintaining their health so sometimes stroke haunt people. At least health facilities that provide facilities for post-stroke patient's recovery into consideration to design the Post-Stroke Rehabilitation Center in Semarang. Although it has a fairly high level of activity, Semarang still has a relative has beautiful environment with low pollution levels that support the existence of post-stroke rehabilitation center. The design concept of arrangement post-stroke rehabilitation center both interior and exterior should be able to provide comfort for patients and visitors, and do not disturb the environment in the surrounding areas. Thus, the existence of post-stroke rehabilitation center can survive and develop so as to provide benefits for society in general.